2004
DOI: 10.1111/j.1365-2672.2004.02344.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of isooctane by Mycobacterium austroafricanum IFP 2173: growth and catabolic pathway

Abstract: Aims: Isooctane (2,2,4-trimethylpentane), a major component of gasoline formulations, is recalcitrant to biodegradation probably because of the quaternary carbon group it contains. Information on the biodegradability of this hydrocarbon is essential to evaluate its fate in the environment. For these reasons, the degradation kinetics and the catabolic pathway of isooctane were investigated in Mycobacterium austroafricanum IFP 2173, the only strain characterized to use it as sole carbon and energy source. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…It also suggested that in R. wratislaviensis IFP 2016 there may be at least two different alkane hydroxylases: one attacking long-chain alkanes (like hexadecane) and having no capacity toward isooctane and the other attacking short-chain alkanes (like octane) and also isooctane. The biodegradability of isooctane is poorly documented; Mycobacterium austroafricanum IFP 2173 is the only strain for which the capacity to grow on isooctane as a sole carbon and energy source has been characterized, and it was shown by reverse transcription-PCR that this probably involved the expression of an alkB gene (43). It is also interesting that isooctane utilization was reduced considerably by the presence of BTEXs (9).…”
Section: Discussionmentioning
confidence: 99%
“…It also suggested that in R. wratislaviensis IFP 2016 there may be at least two different alkane hydroxylases: one attacking long-chain alkanes (like hexadecane) and having no capacity toward isooctane and the other attacking short-chain alkanes (like octane) and also isooctane. The biodegradability of isooctane is poorly documented; Mycobacterium austroafricanum IFP 2173 is the only strain for which the capacity to grow on isooctane as a sole carbon and energy source has been characterized, and it was shown by reverse transcription-PCR that this probably involved the expression of an alkB gene (43). It is also interesting that isooctane utilization was reduced considerably by the presence of BTEXs (9).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting organic acids are most likely metabolized via ␤-oxidation for several reasons: (i) the occurrence of intermediates identified during rubber degradation by S. coelicolor A1 are explainable through degradation via ␤-oxidation; (ii) inhibition by acrylic acid, a ␤-oxidation-specific inhibitor, was observed in strain A1 (18) and other rubber-degrading strains (72); and (iii) ␤-oxidation is also involved in microbial degradation of branched-chain alkanes, such as isooctane (84), pristane (62), phytane (83), squalane, and squalene. The latter is also known to be metabolized by strain VH2 (14).…”
Section: Resultsmentioning
confidence: 99%
“…This result can be partially attributed to the efficiency of the PCR primer pair (Rhose2/ Rhoas1). These primers, previously designed from the alkB sequence of P. putida GPo1 and located between positions Tyr160/Ile166 and Tyr270/Gly275 (Heiss-Blanquet et al 2005;Solano-Serena et al 2004), were less degenerate than the TS2S/deg1RE primer pair (Smits et al 1999) and amplified a smaller DNA fragment (343 bp instead of 525 bp). The polypeptide sequences, deduced from the nucleotide sequences of the PCR amplified fragments, were compared to the corresponding polypeptide fragments of AlkB from M. tuberculosis H37Rv and P. putida GPoI.…”
Section: Alkane Hydroxylases In Mycobacteriamentioning
confidence: 99%
“…PCR amplification of the partial alkB gene was performed using the forward primer Rhose2 (5′-ACG-GSC-CAY-TTC-TAC-RTC-G-3′) and the reverse primer Rhoas1 (5′-CCG-TAR-TGY-TCG-AGR-TAG-3′), previously designed (Heiss-Blanquet et al 2005;Solano-Serena et al 2004). Rhose2 and Rhoas1 were located between positions Tyr160/Ile166 and Tyr270/Gly275, respectively, in the alkB sequence of P. putida GPo1.…”
Section: Total Dna Extractionmentioning
confidence: 99%